Legal Politics Of Providing Social Security For Indonesian Migrant Workers Based On The Concept Of Care Ethics - Muhammad Raka Fiqri (Journal Of Social Science (JoSS), 2024)
This study aims to analyze how the legal politics of social security for Indonesian migrant workers is reviewed based on the concept of ethics of care, this research method uses the Normative Research method with a literature approach, the results of the study show that the provision of social security for Indonesian migrant workers has been carried out by the government in recent political legal developments, but on the one hand social security is only given to the extent of implementing public policy, The regulation of providing social security to Indonesian migrant workers is still considered not to provide social security, especially for the families of migrant workers in terms of social policy if in the future they, namely migrant workers, experience illness, unpaid salaries, to experience slavery, in the study of feminism theory there is criticism based on the concept of ethics of care where the need for the government in this case not only carries out its obligations in terms of public policy, but also in terms of social policy, especially social security for the family resilience of Indonesian migrant workers. The concept of ethics of care in providing social security for the families of migrant workers needs to be applied to the formation of a future policy by the government as mandated by Pancasila, namely in realizing social justice and welfare together (Social Welfare).